Comparative Study between Meiji Restoration in Japan & Colebrooke.Cameron Reforms in Sri Lanka - Colombage, Shirani (My University, 2011)
Japan and Sri Lanka (Ceylon) are two Asian countries. Japan experienced a significant restoration in 1868, called the Merli restoration. After the Meiji restoration it had an economic, social, political and educational development. The Merli restoration is a contributory factor for the endless Japanese courage. In Sri Lanka too there was a reform in 1833, called Colebrooke- Cameron reforms. It also had an impact on economic, social political and educational development. But it failed to produce the same effects as the Meiji restoration in Japan. Sri Lanka is still a developing country while Japan is already a developed country. In this study I wish to explore the similarities and dissimilarities of the Meiji restoration and the Colebrooke- Cameron reforms. An indepth study shows that there are similarities and dissimilarities on the political, economical, social and educational fields. In the conciusion I would like to emphasize that the biggest dissimilarify between the two countries is the political unification. Japan was politically unified while Sri Lanka never did. Since ancient times, Sinhalese people have been considering Sri Lanka as a country meant exclusively for Sinhalese. As a result, the other communities like Tamils, Muslims and Burghers who landed in Sri Lanka for various purposes and settled down here later on were never considered as original inhabitants in Sri Lanka. This undoubtedly resulted in its ethnic problems. The most recent example for this is the Liberation Tigers of Tamil Elam movement. Sri Lanka cannot stand as one nation because of its location. From the ancient period there were so many people who stopped in Sri Lanka amidst their sea voyages to rest. But Japan is not in such a location, Therefore nobody goes to Japan as a resting place in the middle of their voyage